Cementless Oxford medial unicompartimental knee replacement: an independent series with a 5-year-follow-up - Panzram, Benjamin; Bertlich, Ines; Reiner, Tobias; Walker, Tilman; Hagmann, Sébastien; Gotterbarm, Tobias (Archives of orthopaedic and trauma surgery, 2017)
PurposeCemented unicompartmental knee replacement (UKR) has proven excellent long-term survival rates and functional scores in Price et al. (Clin Orthop Relat Res 435:171-180, 2005), Price and Svard (Clin Orthop Relat Res 469(1):174-179, 2011) and Murray et al. (Bone Joint Surg Br 80(6):983-989, 1998). The main causes for revision, aseptic loosening and pain of unknown origin might be addressed by cementless UKR in Liddle et al. (Bone Joint J 95-B(2):181-187, 2013), Pandit et al. (J Bone Joint Surg Am 95(15):1365-1372, 2013), National Joint Registry for England, Wales and Northern Ireland: 10th Annual Report 2013 (http://www.njrcentre.org.uk/njrcentre/Portals/0/Documents/England/Reports/10th_annual_report/NJR%2010th%20Annual%20Report%202013%20B.pdf, 2013), Swedish Knee Arthroplasty Register: Annual Report 2013 (http://www.myknee.se/pdf/SKAR2013_Eng.pdf, 2013).MethodsThis single-centre retrospective cohort study reports the 5-year follow-up results of our first 30 consecutively implanted cementless Oxford UKR (OUKR). Clinical outcome was measured using the OKS, AKSS, range of movement and level of pain (visual analogue scale). The results were compared to cemented OUKR in a matched-pair analysis.ResultsImplant survival was 89.7%. One revision each was performed due to tibial fracture, progression of osteoarthritis (OA) and inlay dislocation. The 5-year survival rate of the cementless group was 89.7% and of the cemented group 94.1%. Both groups showed excellent postoperative clinical scores.ConclusionsCementless fixation shows good survival rates and clinical outcome compared to cemented fixation.